Analisis Peran Semiotika Visual dalam Meningkatkan Kesadaran Masyarakat akan Pengidap Gangguan Kecemasan - Irvan Cristian Hartanto (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2024)
Anxiety disorders are serious psychological conditions that are often overlooked or misunderstood by the public. To raise awareness of anxiety disorders, using visual elements such as photographs and illustrations has become a popular approach. This study used an experimental approach in which participants were exposed to informational materials about anxiety disorders in the form of photographs and illustrations. These visual elements were designed with semiotics to create clear interpretations that the wider community can directly accept. The results of this study are expected to provide better insight into the effectiveness of using visuals in raising awareness of anxiety disorders, as well as its practical implications in mental health education for the community.